Pegs, Baskets, and the Importance of Policy Credibility: Lessons of the 1992-93 ERM Crisis - Ulrich Volz (Hamburg Institute of International Economics (HWWA), 2005)
This paper argues that, in contrast to the popular bipolar view on exchange rate choices, intermediate regimes in general and regional exchange rate systems such as the European Monetary System (EMS) in particular should not be ruled out per se even in today's world of highly mobile capital. The paper highlights that the 1992/93 crisis of the EMS? Exchange Rate Mechanism was a crisis of an exchange rate system and not just the collapse of unilateral pegs pursued by individual countries. Based on an assessment of credibility of the EMS before and during the crisis, the paper discusses distinct features that add to the credibility of regional exchange rate systems. It reasons that a system that is built around well-defined rules, and which is managed very carefully and co-operatively according to those rules, could be both credible and sustainable even in the 21st century.
Keywords: F33; F02; F36; F42; 330; exchange rate regimes; regional monetary systems; EMS crisis; policy credibility; Wechselkurssystem; Europäischer Währungsverbund; Glaubwürdigkeit; Währungskrise; EU-Staaten